Nocardiosis in Cats - Clinical, Anatomopathological and Morphotintorial Characteristics - Firmino, Millena de Oliveira; Frade, Maria Talita Soares; Nascimento, Maria Jussara Rodrigues do; Silva, Raquel Annes Fagundes; Lorenzo, Cíntia de; Pavarini, Saulo Petinatti; Galiza, Glauco José Nogueira de; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2021)
Background: Nocardiosis is an infectious bacterial disease that can cause cutaneous/ subcutaneous, pulmonary and systemic lesions in different species of domestic animals. The type of transmission occurs through mechanical lesions on the skin or contamination of wounds, in cases of skin involvement, inhalation of aerosols and ingestion of contaminated materials are involved in the pathogenesis of the respiratory and digestive form of the disease. This paper described 4 cases of nocardiosis in cats, addressing the clinical, anatomopathological and morphotintorial characteristics of Nocardia sp. Cases: Four cases of nocardiosis in cats were reviewed, in which data related to breed, sex, age, origin, clinical signs, macroscopic and histological lesions described in necropsy protocols were evaluated. The histological tissue sections stained with Hematoxylin and Eosin (HE) were evaluated in order to characterize the inflammatory response in each case. In addition, paraffin blocks of fragments from affected organ were selected to perform special histochemical staining techniques of Grocott Methenamine Silver (GMS), modified Ziehl-Neelsen, Gram Brown-Brenn and Giemsa stain which are the most characterized techniques used for histopathological diagnoses and it was also used an immunohistochemical test with polyclonal antibody anti-Nocardia sp. (non-commercial). The animals were adults of both sexes, mixed breed, not castrated and semi-domesticated. Neither immunosuppressive factors nor concomitant diseases were identified in the cases studied. The main clinical signs were apathy, anorexia, dehydration, phlegmon and draining tracts. Macroscopically, skin / subcutaneous tissue (3/4), skeletal muscle (2/4), lymph nodes (2/4), liver (2/4), omentum (1/4), spleen (1/4) were affected. In addition, it could be noted that mandibular bone (1/4), pleural tissue (1/4), left testicle (1/4) and Central Nervous System (CNS) (1/4) were also affected by this disease. Microscopically, regarding all cases, there was a pyogranulomatous inflammation in the affected organs. With respect to cases 1, 3 and 4, filamentous, branched, slightly basophilic structures in loose or individual aggregates in the interior of the pseudo-rosettes and in the necrotic areas were observed in the HE-stained tissue sections. In all cases submitted to special histochemical techniques, filamentous, branched, individual or loose aggregate structures were observed, the samples were impregnated with silver, and bacteria appear as blue using the Brown-Brenn Gram technique, and stained red in the modified Ziehl-Neelsen, and stained faintly pink in Giemsa stain. The bacteria were observed mainly in the border of the pyogranulomas, in the center of the pseudo-rosettes and in the necrotic areas, being compatible with the infection by Nocardia sp. All cases were positive for immunohistochemistry (IHC). Discussion: Nocardiosis was diagnosed in all cats in this study based on the anatomopathological findings associated with the visualization of the agent and its morphotintorial characteristics by using special histochemical stains and being confirmed by IHC. It occurs mainly in the cutaneous and/or subcutaneous tissues, with systemic involvement and death of the affected animals, in addition to affecting bone tissue considered an uncommon site for the disease. The diagnosis can be established based on the anatomopathological findings associated with the morphotintorial characteristics by using special histochemical stains, which are important for evidencing and morphologically characterizing the agent, as well as being confirmed by IHC. Keywords: disease in cat, pyogranulomatous inflammation, Nocardia sp. Título: Nocardiose em gatos - achados clínicos, anatomopatológicos e morfotintoriais Descritores: doença de gato, inflamação piogranulomatosa, Nocardia sp.